PENGEMBANGAN KOMITMEN ORGANISASI DALAM IMPLEMENTASI PENDIDIKAN KARAKTER DI SEKOLAH KESATUAN BANGSA (KESATUAN BANGSA SCHOOL) YOGYAKARTA (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
Teachers Commitment in determining the success of a character education at schools is very important because teachers are those who implement education at schools . Teachers are the ones who are in direct contact with students. One of the key factor to increase teachers’ commitment can be done by the principal by maintaining and improving teacher’s commitment, so the goal of character education programs in schools can be achieved.This study aims at (1) determining the development of organizational commitment in the context of the implementation of character education at Kesatuan Bangsa Boarding School (KBBS) Yogyakarta, (2) describing the principal’s effort in giving the example and values to his subordinates. In order to implement the character education in KBBS Yogyakarta, (3) understanding the constraints faced by Kesatuan Bangsa Boarding School Yogyakarta in implementing the character educationThis study was conducted by qualitative research approach. The process of data collection in the field using interviews, observation and documentation as well as involving the principal, teachers and students. The results showed that the character education in Kesatuan Bangsa Boarding Scool Yogyakarta was implemented with a good teacher commitment. Education in the school system with a boarding school model requires that teachers take an active role in both academic and non-academic activities, especially in habituation good life. Efforts to increase teacher commitment were demonstrated in several ways, namely: 1) the creation of a family atmosphere, 2) quality education system, 3) the welfare of teachers assuredness , 4) the creation of teacher development, and 5) teachers the opportunity to develop themselves . As for the obstacles still facing teachers is uneven readiness related fulltime work, and in general the influence of the media, especially television and the internet in certain limits troubling teachers because the values promoted in the media often conflict with the national character of Indonesia.